2019
DOI: 10.1017/sjp.2019.13
|View full text |Cite
|
Sign up to set email alerts
|

Autism and Faux Pas. Influences of Presentation Modality and Working Memory

Abstract: People diagnosed with an autism spectrum disorder (ASD) often have difficulties on Theory of Mind (ToM) tasks involving social situations, such as ‘faux pas’. The objective of this study was to find the modality of presentation (visual, verbal, or mixed) that yields the best understanding of a ‘faux pas’, and the possible influence of other variables, including intelligence (IQ), age, and working memory. Thirty autistic children and 30 neurotypical children, all aged 7 to 12 years old and comparable in age and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 32 publications
1
9
0
6
Order By: Relevance
“…Cognitive domains that are often affected in ASD include social cognition, executive functioning, processing speed, language and sensory processing (Hill and Frith, 2003). It has been suggested that poor cognitive abilities may contribute to the social and communication impairments commonly found in individuals with ASD (Clarke et al , 2016; Garcia-Molina and Clemente-Estevan, 2019; Haigh et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive domains that are often affected in ASD include social cognition, executive functioning, processing speed, language and sensory processing (Hill and Frith, 2003). It has been suggested that poor cognitive abilities may contribute to the social and communication impairments commonly found in individuals with ASD (Clarke et al , 2016; Garcia-Molina and Clemente-Estevan, 2019; Haigh et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Esta predicción de las variables FC y CI corrobora la importancia de entender la interacción respecto a los aspectos afectivo-sociales y mentalistas de los personajes, y por otro lado, la comprensión gramatical y pragmática ligada a la intención del hablante (al lenguaje representado por la prueba Vocabulario). Algunos estudios que analizaron tareas de TM cognitivamente más complejas, han argumentado su dificultad por la influencia de la memoria de trabajo verbal en el recuerdo de la historia (García-Molina & Clemente, 2019a;Ozonoff, Pennington, & Rogers, 1991). Otra interpretación posible de las diferencias encontradas en las dos pruebas de CI vendría explicada por la teoría de la Coherencia Central Débil ([CCD];Frith, 1989), que según el investigador abordaría la justificación de cómo las personas con autismo procesan la información de su entorno, atendiendo a detalles locales y con dificultades para extraer un significado general, es decir, podrían ver las partes, pero no el todo.…”
Section: Discussionunclassified
“…Además, se denotó cierta culpa e intencionalidad en sus explicaciones hacia Inés, hecho que se correspondería con los hallazgos en Zalla et al (2009), con descripciones maliciosas y términos no apropiados hacia el personaje, observándose además que el Grupo 2 dio más respuestas inapropiadas en este sentido (frases más cortas y ofensivas) que el Grupo 1 (ver resultados en hipótesis 2(b) para más ejemplos). Este patrón de "sobre-culpa" (la tendencia a considerar al otro más "malo" de lo que realmente es) seguiría nuevamente la línea de los problemas en ToM, pues las personas con TEA emitirían su juicio sobre los otros basándose más en los resultados (lo que ha dicho está mal) que en las intenciones (esa persona no sabía / no tenía información sobre ello y, por tanto, no lo hizo a propósito) (Buon et al, 2013;García-Molina & Clemente, 2019a;Li et al, 2018;Margoni & Surian, 2016).…”
Section: Discussionunclassified
See 2 more Smart Citations